ACTIVATION OF VASTUS MEDIALIS OBLIQUES AT DIFFERENT KNEE ANGLES IN CLOSED KINETIC CHAIN AND OPEN KINETIC CHAIN POSITION IN SUBJECTS WITH PATELLO FEMORAL PAIN SYNDROME (International Journal of Physiotherapy, 2015)
Background: Patello femoral pain syndrome is one of the most common musculoskeletal disorders and is reported to affect 15% - 33% of an active adult population and 21%-45% of adolescents thereby decreasing the work capacity of an individual. Patello femoral pain syndrome as implicated is due to inappropriate neural control of the quadriceps femoris muscle. Since Vastus medialis muscle is regarded as the dynamic medial stabilizer of patella so it’s important to understand the activation of Vastus Medialis Oblique’s in patients with patello femoral pain syndrome The purpose of this study is to assess the activation of Vastus Medialis Oblique’s at different knee angles between closed kinetic chain position and open kinetic chain position and the information thus gained can be used to design training program aimed at controlling patello femoral joint dysfunction.Methods: Thirty subjects with patello femoral pain syndrome (assessed through history and examination) were assigned to two groups. Group A was made to perform open kinetic chain activity(i.e. sitting on high plinth) and Group B was made to perform a closed kinetic chain activity(i.e. standing) The outcome measure were amplitude and duration. Analyses were performed using independent t-Test.Results: Significant difference was found between the groups for amplitude and duration at varying angles. Amplitude: 0 degree (p=0.004), 60 degrees (p=0.015), 90 degrees (p=0.004). Duration: 0 degree (p=0.007), 60 degrees (p=0.008),90 degrees (p=0.002)Conclusion: Based on the outcome of the study it’s concluded that there is greater activation of Vastus Medialis Oblique’s muscle while performing close kinetic chain activity than in open kinetic chain.